The Role of Civil and Political Freedoms in Combating Tyranny (Mauritania as a Case Study) - El Mokhtar Ballaty , Mohamed (Journal of Legal Studies and Researches, 2026)
Civil and political freedoms are safeguards against tyranny, allowing individuals to act within a legitimate sphere recognized by public authorities. This research aims to study the role of freedoms in limiting tyranny, based on a legal science methodology. We have concluded that freedoms play an essential role in limiting tyranny, but that this role is linked to the functioning of institutions and may remain relative on this basis.